Prospective application of palm oil mill boiler ash as a biosorbent: effect of microwave irradiation and palm oil mill effluent decolorization by adsorption - Hamzah, Muhammad Hazwan; Ahmad Asri, Muhammad Fitri; Che Man, Hasfalina; Mohammed, Abdulsalam (MDPI, 2019)
Common conventional biological treatment methods fail to decolorize palm oil mill effluent (POME). The present study focused on using the abundant palm oil mill boiler (POMB) ashes for POME decolorization. The POMB ashes were subjected to microwave irradiation and chemical treatment using H2SO4. The resultant adsorbents were characterized using scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX), and Brunauer–Emmett–Teller (BET) analyses. The adsorption efficiency was evaluated at various pH levels (2–8.5), adsorption dosages (3–15 g) in 200 mL, and contact times (1–5 h). The microwave-irradiated POMB-retained ash recorded the highest color removal of 92.31%, for which the best conditions were pH 2, 15 g adsorbent dosage in 200 mL, and 5 h of contact time. At these best treatment conditions, the color concentration of the treated effluent was analyzed using the method proposed by the American Dye Manufacturers Institute (ADMI). The color concentration was 19.20 ADMI, which complies with the Malaysia discharge standard class A. The Freundlich isotherm model better fit the experimental data and had a high R2 of 0.9740. Based on these results, it can be deduced that microwave-irradiated POMB-retained ash has potential applications for POME decolorization via a biosorption process.